2019
DOI: 10.2147/dmso.s203937
|View full text |Cite
|
Sign up to set email alerts
|

<p>Obesity, adipocyte hypertrophy, fasting glucose, and resistin are potential contributors to nonalcoholic fatty liver disease in South Asian women</p>

Abstract: Purpose: Nonalcoholic fatty liver disease (NAFLD) is often referred to as the hepatic manifestation of the metabolic syndrome. The relationship between body weight, NAFLD, and insulin resistance is not well characterized in humans. Additionally, it is unclear why South Asians develop these complications at lower levels of obesity compared to their Western counterparts. Patients and methods: To address this question, we performed a cross-sectional study using a convenience sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 61 publications
2
11
0
Order By: Relevance
“…Adipocyte hypertrophy is an adaptive adipose tissue response to the excess of energy and correlates positively with metabolic syndrome manifestations [ 30 , 31 , 32 , 33 ]. Since, in our study, the curcumin-supplemented diet resulted in body weight and fat mass reduction in mice, we evaluated the effects of curcumin on adipocyte hypertrophy in white epididymal adipose tissue.…”
Section: Resultsmentioning
confidence: 99%
“…Adipocyte hypertrophy is an adaptive adipose tissue response to the excess of energy and correlates positively with metabolic syndrome manifestations [ 30 , 31 , 32 , 33 ]. Since, in our study, the curcumin-supplemented diet resulted in body weight and fat mass reduction in mice, we evaluated the effects of curcumin on adipocyte hypertrophy in white epididymal adipose tissue.…”
Section: Resultsmentioning
confidence: 99%
“…In 2019, the Taiwanese scholar Hsu CL and his team found an association between FPG and NAFLD in 4000 nonobese people [18]. Additionally, a study from Sri Lanka reported the incidence of NAFLD in 34 local women; after post hoc analysis, it was found that there was a correlation between higher FPG and NAFLD [19]. Similar findings have been reported in China [24]; although these studies have highlighted that there is a positive correlation between FPG and NAFLD, these studies still have some limitations: (1) the adjustment of potential confounding factors, such as LDL-C, ALB, GLB, and DBP, is not sufficient; (2) the participants were not entirely nonobese, and the association between normal lipids and the incidence of NAFLD was not evaluated;…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some clinical studies from Sri Lanka and Taiwan have reported an association between FPG and the development of NAFLD. The reports argued that higher FPG is a significant risk factor for NAFLD [18,19]. However, the sample size of these studies was relatively small, and similar studies are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that FLD, together with type II diabetes and insulin resistance, is associated with a higher risk of death (2). There are limited studies on FLD in Iran (15), and there is a lack of a consensus regarding the relationship between insulin resistance and fatty liver disease (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%